1999
DOI: 10.1046/j.1365-2567.1999.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage–tumour cell interactions: identification of MUC1 on breast cancer cells as a potential counter‐receptor for the macrophage‐restricted receptor, sialoadhesin

Abstract: SUMMARYIn many carcinomas, infiltrating macrophages are commonly found closely associated with tumour cells but little is known concerning the nature or significance of adhesion molecules involved in these cellular interactions. Here we demonstrate in primary human breast cancers that sialoadhesin (Sn), a macrophage-restricted adhesion molecule, is frequently expressed on infiltrating cells that often make close contact with breast carcinoma cells. To determine whether Sn could act as a specific receptor for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
82
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 36 publications
2
82
0
1
Order By: Relevance
“…Whether the increased expression of ST3Gal-I, which we have identified in breast cancers, affects function, possibly by affecting cell interactions, is unclear. Certainly core 1 carrying a sialic acid in ␣2,3 linkage is a major ligand for sialoadhesin, and MUC1 carrying such glycans interacts well with this sialic acid binding protein found on macrophages, which can be found as infiltrates in a proportion of breast cancers (37).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the increased expression of ST3Gal-I, which we have identified in breast cancers, affects function, possibly by affecting cell interactions, is unclear. Certainly core 1 carrying a sialic acid in ␣2,3 linkage is a major ligand for sialoadhesin, and MUC1 carrying such glycans interacts well with this sialic acid binding protein found on macrophages, which can be found as infiltrates in a proportion of breast cancers (37).…”
Section: Discussionmentioning
confidence: 99%
“…Mucin-type membrane glycoproteins have been shown to exhibit both anti-adhesive and cell-cell adhesive properties (Baumhueter et al, 1994;Gendler and Spicer, 1995;Nath et al, 1999). The anti-adhesive function of large transmembrane mucins, such as episialin (MUC1), epiglycanin, and sialomucin, is attributable to their masking cell adhesion receptors because of their large extended ectodomains and to the repulsive forces provided by sialic acid (Kemperman et al, 1994;Komatsu et al, 1997;Wesseling et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This extended structure is expected to act as a particularly effective scaffold for the presentation of oligosaccharide chains to lectins, thereby promoting interactions between cancer cells and appropriate lectinexpressing cells. It has been reported that MUC1 is a natural ligand of endogenous Siglec-1 (14) and galectin-3 (15,16) and that the binding of galectin-3 increases the adhesion between cancer cells and endothelial cells and the aggregation of tumor cells. However, these studies provided no insights to the downstream signaling by MUC1 after binding of these lectins.…”
mentioning
confidence: 99%